Supramolecular structures and self-association processes in polymer systems - Hrubý, M; Filippov, S K; Štěpánek, P (Physiological research, 2016)
Self-organization in a polymer system appears when a balance is achieved between long-range repulsive and short-range attractive forces between the chemically different building blocks. Block copolymers forming supramolecular assemblies in aqueous media represent materials which are extremely useful for the construction of drug delivery systems especially for cancer applications. Such formulations suppress unwanted physicochemical properties of the encapsulated drugs, modify biodistribution of the drugs towards targeted delivery into tissue of interest and allow triggered release of the active cargo. In this review, we focus on general principles of polymer selforganization in solution, phase separation in polymer systems (driven by external stimuli, especially by changes in temperature, pH, solvent change and light) and on effects of copolymer architecture on the self-assembly process.
Keywords: Polymers; Nanoparticles; Hydrophobic and Hydrophilic Interactions; nanočástice; Drug Delivery Systems; polymery; povrchově aktivní látky; Surface-Active Agents; lékové transportní systémy; hydrofobní a hydrofilní interakce